Proposed Political Marketing Strategy to Attract Millennial Voters: Case Study Indonesia Democratic Party of Struggle (PDIP) (The Indonesian Journal of Business Administration, 2020)
The Indonesian Democratic Party of Struggle (PDIP) was established in 1999 by Megawati Soekarnoputri with a good performance for the last 20 years with its superiority in a lower class society with its tagline “Partainya Wong Cilik”. PDIP has succeeded won three general elections consisting of 1999, 2014, and 2019.The problem facing for PDIP in the coming years to attract educated millennial groups because in 2024 the Indonesian Central Board of Statistics (BPS) predicted the millennial generation will be contributed 60 percent of Indonesia’s total population. Meanwhile in recent years has been a massive shifting from conventional media to internet media as a media platform for the political campaigns and the current internet media user dominated by the millennial generation. Furthermore, new political figures will emerge in the Indonesian Political and the other parties will be more competitive. Therefore, this research tries to find appropriate political marketing strategies for PDIP to attract millennials.This research using mixed methods research to support the accuracy of the analyses. The author uses STP (Segmenting, Targeting, Positioning) analysis to comprehend PDIP’s internal conditions and issues. While to comprehend PDIP’s external conditions and issues, the author uses Porter’s Five Forces analysis. The results of all analyses are developed using TOWS Matrix analysis so that it becomes several alternative strategies. Based on all analyses, the root of the problem facing PDIP is the unattractive political marketing for millennials. Therefore, the author proposed three political marketing strategies consist of maintaining traditional and base voters, build internal political programs by millennials preference, and developing digital political strategies. Key Words: political marketing, millennials, political party, social media, general election